John Paul II and respect for local cultures - María Inés Franck (Chrześcijaństwo-Świat-Polityka)
The cultural issue has undoubtedly been one of the main ideas of John Paul II's pontificate. This paper reviews the main definitions of culture that the Polish Pope left us, relating them to the identity of peoples. In this same sense, a brief analysis of the phenomenon of globalization is made as it was developed by John Paul II, and it ends with a brief reference to the impact of this phenomenon on local cultures.